Between illegality and recognition: Exploring sacrificial violence in a Manila brotherhood. (March 2015) - Jensen, Steffen
This article explores how poor, young men in a Manila relocation site enter into a brotherhood as a means to claim recognition from dominant society. It argues that by joining the brotherhood, which emanates out of a Greekletter fraternity tradition in US and Philippine universities, the young men establish a link to people and networks in power. Drawing on ritual and religious sacrifice theory, the article illustrates how sacrificial violence in initiation rites becomes a performance of worth. This performance of valour and worth do indeed reach dominant society. After exploring the initiation ritual of the young men the article then turns to explore the nature of the Philippine elite. This analysis suggests that while there are several, often competing strands within elite politics (legalistic, moralistic and clientelist), the efforts of the young men end up confirming and reproducing the elite and their own marginalization as unruly, uncouth goons of political machines.